2010
DOI: 10.1002/jhm.780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an educational program and a standardized insulin order form on glycemic outcomes in non‐critically ill hospitalized patients

Abstract: Disclosure: Nothing to report. BACKGROUND:The optimal approach to managing hyperglycemia in noncritically ill hospital patients is unclear. OBJECTIVE: To investigate the effects of targeted quality improvement interventions on insulin prescribing and glycemic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Glycaemic control for hospitalized patients is multifactorial: patients may not comply with diet orders, monitoring or treatment. Successful interventions incorporated education with the introduction of a multi-specialty targeted glycaemic management [18], routine rounds on hyperglycaemic patients with an attending endocrinologist [19], improvements with computerized order entry systems [20], introduction of insulin order sets [21] and insulin order forms [22]. While our data confirm previous findings when training residents, they are limited by the number of analysed patient visits and singlecentre study design.…”
Section: Discussionsupporting
confidence: 79%
“…Glycaemic control for hospitalized patients is multifactorial: patients may not comply with diet orders, monitoring or treatment. Successful interventions incorporated education with the introduction of a multi-specialty targeted glycaemic management [18], routine rounds on hyperglycaemic patients with an attending endocrinologist [19], improvements with computerized order entry systems [20], introduction of insulin order sets [21] and insulin order forms [22]. While our data confirm previous findings when training residents, they are limited by the number of analysed patient visits and singlecentre study design.…”
Section: Discussionsupporting
confidence: 79%
“…23 Studies by others have shown that a combination of structured insulin orders combined with staff education to partially alleviates clinical inertia in the hospital. [24][25][26][27][28][29] Our facility implemented computerized order entry in 2007 that includes provisions to order basal, prandial, and correction insulin treatment that are accessible to all practitioners. However, despite all these efforts at our institution, clinical inertia remains evident among the inpatient surgical practices.…”
Section: Discussionmentioning
confidence: 99%
“…The types of intervention varied, as well as the implementation strategies, and measures of improvement between studies (see Table S4). Although three studies [19] x Courtenay 2007 [17] x x Donihi 2006 [26] x x Dooley 2011 [28] x Donsa 2016 [27] x x Doyle 2014 [54] x x x x Ena 2009 [41] x x Gomez-Huelgas 2014 [55] x x Guerra 2010 [43] x x x Hamilton 2013 [18] x Harbin 2015 [36] x x Helmle 2017 [37] x x x x x x x Horton 2015 [44] x Kowiatek 2001 [29] x x x x Lehnbom 2009 [35] x x Mamillapalli 2012 [38] x Maynard 2009 [45] x x x McIver 2009 [30] x x x Mulla 2015 [39] x x x Newsom 2018 [15] x x x x Noschese 2008m [46] x x Rushmer 2008 [31] x x x Schnipper 2009 [47] x x x Schnipper 2010 [48] x Taylor 2012 [32] x Thompson 2009 [49] x x x Trujillo 2008 [50] x x Tully 2018 [33] x x x Vaidya 2012 [56] x Valgardson 2015 [52] x x Wesorick 2010 [34] x x Wexler 2010 [52] x Wong 2016 [40] x x Yeung 2018 [53] x x ª 2019 Diabetes UK used the UK's National Inpatient Diabetes Audit (NaDIA) methodology and data collection tool, the follow-up period, interventions, implementation and the data reported were varied, hence it was difficult to pool data or make meaningful comparisons [18,19,32]. The introduction of simple, small focused interventions led to an improvement in the completeness and accuracy of insulin prescribing, particularly when they involved 'hard stops' (such as pre-printi...…”
Section: Interventions To Improve Insulin Prescribing Accuracy and Comentioning
confidence: 99%